Kompos Berbahan Dasar Lumpur Sawit menggunakan Microbakter Alfaafa (M-11) Bagi Masyarakat - Sri Suryaningsih Djunu (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2021)
The purpose of this service is to increase the knowledge and skills of farmers in utilizing palm oil waste to be used as organic fertilizer or compost. Service participants are directed to carry out each technological process themselves in processing palm oil waste into compost. The result of the pre-test was that 15,00% of the participants had knowledge in waste management. The post test results illustrate that 98.00% of participants can understand the activity. In the activity of making compost from oil palm mud using mycobacteria alfaafa (M-11), there were 5% of participants who had knowledge about composting. After counseling in the form of practice, 95.00% of participants were able to make and carry out composting activities. Making compost based on palm oil sludge in Pangeya village, Wonosari sub-district, Boalemo district can add insight and knowledge of farmers and ranchers about how to handle palm oil sludge that pollutes the surrounding environment. Keywords: Compost, palm oil sludge, knowledge